Comparative analysis of mesenchymal stem cells from bone marrow, cartilage, and adipose tissue - Peng, Linyi; Jia, Zhuqing; Yin, Xinhua; Zhang, Xin; Liu, Yinan; Chen, Ping; Ma, Kangtao; Zhou, Chunyan (Stem cells and development, 2008)
Mesenchymal stem cells (MSCs) isolated from bone marrow (BM), cartilage, and adipose tissue (AT) possess the capacity for self-renewal and the potential for multilineage differentiation, and are therefore perceived as attractive sources of stem cells for cell therapy. However, MSCs from these different sources have different characteristics. We compared MSCs of adult Sprague Dawley rats derived from these three sources in terms of their immunophenotypic characterization, proliferation capacity, differentiation ability, expression of angiogenic cytokines, and anti-apoptotic ability. According to growth curve, cell cycle, and telomerase activity analyses, MSCs derived from adipose tissue (AT-MSCs) possess the highest proliferation potential, followed by MSCs derived from BM and cartilage (BM-MSCs and C-MSCs). In terms of multilineage differentiation, MSCs from all three sources displayed osteogenic, adipogenic, and chondrogenic differentiation potential. The result of realtime RT-PCR indicated that these cells all expressed angiogenic cytokines, with some differences in expression level. Flow cytometry and MTT analysis showed that C-MSCs possess the highest resistance toward hydrogen peroxide -induced apoptosis, while AT-MSCs exhibited high tolerance to serum deprivation-induced apoptosis. Both AT and cartilage are attractive alternatives to BM as sources for isolating MSCs, but these differences must be considered when choosing a stem cell source for clinical application.